PkM Optimalisasi Gaya Belajar Visual Siswa Melalui Media Non-Elektronik Metaplan di MI Nurul Mun’im Paiton - Zakiyah BZ; Halimatus Sa’diyah; ST. Romlah; Nur Aini Sofiah Zanjabila (Yayasan Literasi Altruis Khatulistiwa, 2025)
This community service activity aims to enhance learning effectiveness through the use of non-electronic media based on metaplan to optimize students’ visual learning styles at MI Nurul Mun’im Paiton, Probolinggo Regency. The location was chosen based on preliminary observations showing a lack of attention to learning style differentiation—particularly visual learners—and limited access to electronic learning media within the madrasah environment. The activity employed a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation of classroom learning processes, and analyzed through data reduction, presentation, and verification stages. The results show that the application of metaplan successfully increased students’ active participation, clarified conceptual understanding, and fostered creativity in expressing ideas visually. Through metaplan corner activities, students could write or illustrate their understanding of the lessons taught. The use of metaplan proved to be an effective solution for teachers to deliver simple yet meaningful visual learning, especially in schools with limited technological facilities. This program provides practical contributions to the development of innovative learning methods in madrasahs, making them more adaptive to diverse learning styles